2002
DOI: 10.1063/1.1501121
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and diffractive scattering of H2 from Pt(111) studied using a six-dimensional wave packet method

Abstract: We present results of calculations on dissociative and rotationally ͑in͒elastic diffractive scattering of H 2 from Pt͑111͒, treating all six molecular degrees of freedom quantum mechanically. The six-dimensional ͑6D͒ potential energy surface was taken from density functional theory calculations using the generalized gradient approximation and a slab representation of the metal surface. The 6D calculations show that out-of-plane diffraction is very efficient, at the cost of in-plane diffraction, as was the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 63 publications
6
144
0
Order By: Relevance
“…52) and quasi-classical (QC) dynamics. 53 Stateto-state quantum scattering probabilities have been obtained using a time-dependent wave packet method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…52) and quasi-classical (QC) dynamics. 53 Stateto-state quantum scattering probabilities have been obtained using a time-dependent wave packet method.…”
Section: Methodsmentioning
confidence: 99%
“…53 Stateto-state quantum scattering probabilities have been obtained using a time-dependent wave packet method. 54 In the implementation used, 52 the wave packet is propagated according to the time-dependent Schrödinger equation using the split operator method. 55 The method uses a direct product discrete variable representation (DVR) to represent the dependence of the wave function on the center of mass coordinates (X, Y, Z) and the internuclear distance r (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[18] And in a theoretical study of the early barrier system H 2 /Pt(111), a vibrational enhancement of about 20% was found. [19] In both cases, the authors argued that the enhancement of the reactivity upon molecular vibrational excitation is due to vibrational softening.…”
Section: Introductionmentioning
confidence: 99%
“…The optical absorption spectrum of Au 24 nanocluster protected by the mixed ligands of phosphine and thiolate was theoretically reproduced and interpreted (43). Most interestingly, ultrafast luminescence dynamics of thiolate protected Au 25 clusters indicated that their luminescence decay traces showed unique ultrafast growth and decay kinetics that are absent in the larger Au clusters (44). A fast and slow luminescence decay of Au nanocrystals (NCs) was determined originating from recombination of the linear Au-S bond and the staple motif, respectively (45).…”
Section: Introductionmentioning
confidence: 91%
“…Small Pd nanoclusters deposited on solid supporting surfaces, such as MgO (21) or TiO 2 (22,23), were also theoretically studied since it was believed to be responsible for the majority of catalytic activity. The behavior characteristic to the clusters comes from a large fraction of surface atoms and the discrete nature of electronic states, which makes the electronic state of the cluster quite different from those of the bulk structure (24,25).Metal clusters with an appropriate size would be an excellent representation of the metal nanoparticles (26). The 13-atom clusters have drawn much attention because it can form closed-shell icosahedral structure (27,28)and are considered as being representative of highly dispersed metal catalysts (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%